Paclitaxel, cisplatin, and epirubicin first-line chemotherapy in Stage III and IV ovarian carcinoma: Long term results of a phase II study - Papadimitriou, C.A.; Moulopoulos, L.A.; Vlahos, G.; Voulgaris, Z.; Kiosses, E.; Georgoulias, N.; Gika, D.; Diakomanolis, E.; Michalas, S.; Dimopoulos, M.A. (Cancer, 2000)
BACKGROUND. The combination of paclitaxel with cisplatin or carboplatin has become the preferred chemotherapy regimen in the treatment of epithelial ovarian carcinoma. Anthracyclines also have activity in this disease. We conducted a Phase II study by using the combination of paclitaxel, cisplatin, and epirubicin for the treatment of advanced ovarian carcinoma. METHODS. Forty consecutive patients with optimally (n = 7) or suboptimally (n = 33) debulked advanced ovarian carcinoma (International Federation of Gynecology and Obstetrics (FIGO) Stage III or IV) were treated with paclitaxel, 135 mg/m2, as a 3-hour intravenous infusion, cisplatin 75 mg/m2 intravenously (i.v.), and epirubicin 50 mg/m2 i.v. every 3 weeks on an outpatient basis. Granulocyte-colony stimulating factor was administered at a dose of 5 μg/kg/day on Days 5-9. RESULTS. Among 28 patients with measurable disease, 24 (86%%) achieved an objective response including 19 complete and 5 partial responses. Among 18 patients who underwent reassessment laparotomy, pathologic complete response was confirmed in 9 patients. At a minimum follow-up of 40 months, the median overall survival had not been reached whereas the median time to progression for all patients was 18.7 months. The median remission duration for women with measurable disease who responded to treatment was 14 months. The treatment was well tolerated without toxic deaths; the most common toxicity was Grade 3/4 neutropenia that occurred in 30% of patients. Significant neuropathy (Grade 2 or higher) developed in only 8% of patients. CONCLUSIONS. The combination of paclitaxel, cisplatin, and epirubicin is a well tolerated outpatient regimen with significant activity in the treatment of advanced epithelial ovarian carcinoma. (C) 2000 American Cancer society.
Keywords: Cisplatin; Epirubicin; Epithelial ovarian carcinoma; Paclitaxel